Cytokines and related signaling pathways in traumatic brain injury - Zhu, Lihong; Huang, Siyun; Chen, Weiqiang; Li, Kangsheng; Sheng, Jiangtao (Frontiers in Immunology, 2026)
Traumatic brain injury (TBI) represents a critical public health challenge with profound consequences for patients’ neurological function and quality of life. The delayed secondary injuries following TBI can lead to devastating long-term sequelae encompassing cognitive deficits, emotional disturbances, post-traumatic epilepsy, and neurodegeneration manifested as Alzheimer’s disease or Chronic Traumatic Encephalopathy (CTE). Emerging evidence highlights neuroinflammation as a pivotal mechanism driving secondary injury progression, establishing it as a prime therapeutic target in TBI management. Central to this process is the dysregulated cytokine release and associated signaling cascades that orchestrate neuroinflammatory responses. The pathological persistence of neuroinflammation arises from chronic glial activation and sustained immune cell infiltration following TBI. This review systematically examines recent advances in understanding cytokine dynamics and their regulatory pathways across different temporal phases of TBI-induced neuroinflammation. Notably, cytokines exhibit temporal functional pleiotropy - the same inflammatory mediators may exert diametrically opposed effects during acute (<24h), subacute (1-7d), and chronic (>7d) post-injury phases. This temporal dichotomy underscores the critical importance of precision timing when implementing cytokine-targeted therapies. Our comprehensive analysis integrates current clinical, preclinical and basic research evidence to illuminate potential mechanisms underlying TBI-associated neuropathology. We propose that multi-modal therapeutic strategies should combine spatiotemporal regulation of cytokine activity with pathway-specific interventions. This approach could potentially disrupt the self-perpetuating cycle of neuroinflammation while preserving beneficial reparative functions. The synthesis presented herein provides a framework for developing chronotherapeutic interventions against TBI-related neural dysfunction.